Evaluation of a clinical pharmacist consultation service for patients with infectious diseases in China: a systematic review and meta-analysis. Issue 3 (20th June 2019) - Zhang, Jiaxing; Li, Xiaosi; Xie, Juan; Zheng, Wenyi
Abstract : Background: Since antibiotic resistance has become a global public health issue, a clinical pharmacist consultation service has been established in China. Objectives: To clarify the role of the clinical pharmacist consultation service in the management of infectious diseases (ID). Methods: Medline, Embase, Cochrane Library, Chinese National Knowledge Infrastructure, Chinese Biomedical Database, Vip Database and Wanfang Database were searched for studies meeting predefined inclusion criteria. The pooled acceptance rate of consultation (ARC) and effective rate of patients treated with the acceptance of pharmacists' suggestions (ERA) were then calculated. Results: Fifty studies (involving 8616 patients and 8828 consultations) from 17 different provinces in China were included. The pooled ARC and ERA were 93.13% (95% CI 90.62% to 95.00%) and 93.60% (95% CI 91.99% to 95.24%), respectively. Adopting pharmacists' suggestions can significantly improve the prognosis of patients with ID with a risk ratio of 2.08 (95% CI 1.41 to 3.06). Factors such as study time, characteristics of the research institution and patients have important influences on ARC. Conclusion: Prospective cohort studies with better methodology are needed, although a series of uncontrolled studies has shown that the service has excellent acceptance and improves the effectiveness of treatment for ID.